Non-linear analysis of laminated composite doubly curved shallow shells - Bich, Dao Huy (Vietnam Journal of Mechanics, 2006)
This paper deals with governing equations and approximate analytical solutions based on some wellknown assumptions to the non-linear buckling and vibration problems of laminated composite doubly curved shallow shells. Obtained results will be presented by analytical expressions of the lower critical load, the postbuckling load-deflection curve and the fundamental frequency of non-linear free vibration of the shell